บทบาทของโรงเรียนพุทธศาสนาวันอาทิตย์ในการขัดเกลาทางศีลธรรม : ศึกษากรณีนักเรียนชั้นมัธยมศึกษาในเขตกรุงเทพมหานคร - จุฑารัตน์ ไพศาลโรจนรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this thesis are to study the role of Sunday Buddhist Schools in moral socialization of Thai youths, the public-service role of temples to modern Thai society and especially to Thai youths in Buddhist activities participation. It also tries to inquire supplementary factors which encourage Thai youths to attend the Sunday Buddhist Schools. This research used anthropological techniques in data accumulation and analysis. Participant observation and non-participant observation and in-depth interviews were executed with a group of 9 male and female students from Mahamongkuta Sunday Buddhist Studies Centre and Mahachula Sunday Buddhist School, age between 12-18 years old. In addition to another 15 cases of parents, friends and teachers. The study revealed that both Sunday schools played essential role in youths moral socialization. The Sunday school project was highly appreciated as another social service of the temples to modern Thai society and as the promoting agent in Buddhist activities to the youths. The study also found that in addition to religious knowledge, the need to gain more skill in Thai music, foreeign and other subjects, was the motive of the students who attended the Sunday Buddhist School.